Service Quality and Performance Results through Customer Satisfaction at Small-Scale Hotels in Hanoi Area (International Journal of Scientific Research and Management (IJSRM), 2023)
In the context of the Covid-19 pandemic, the hotel industry in Vietnam shows a strong recovery, businesses are continuously stepping up recruitment activities, expanding markets and increasing customer files. . The goal of the article is to clarify the impact of service quality on operational results through customer satisfaction. The research sample was collected by the author of the article from 119 survey questionnaires after 3 times distributing questionnaires to customers who used services at 5 small-scale hotels in the Hanoi area of ​​Vietnam. Using quantitative research on the PLS-SEM linear structural model on SPSS 20 and AMOS 20 software, the results have identified 3 groups of recommended solutions for hotel managers in meeting demand. customers and improve operational results, including: (i) Organizing hotel staff, foreign language training, and professional behavior; (ii) Invest in equipment and facilities suitable to customer needs in different stages; (iii) Increase customer responsiveness, especially through the internet channel.